The association between resilience and performance: the mediating role of workers’ well-being - Cantante-Rodrigues, Francisca (2021)
Associations among resilience, employee well-being (i.e., work engagement and burnout), and performance were examined. Up to date, to the best of our knowledge, no studies were carried out exploring the relationship between all three constructs into the same model from an organizational perspective. Consequently, the principal aim of this study was to understand and provide evidence regarding the above-mentioned relationships. Data were collected from a sample of 249 working professionals. The findings showed a positive relationship between resilience and work engagement, and a negative relationship between resilience and burnout. However, while work engagement was found as being positively and significantly related to performance, the relationship between burnout and performance was not significant. Additionally, work engagement seems to partially mediate the relationship between resilience and performance, since a significant direct relationship between resilience and performance was also observed. The practical and theoretical implications of these findings are discussed.